Editorial Vol.1(1) - Subedi, Narendra Raj; Dahal, Arvind; Labh, Bhabes Kumar (The Saraswati Review, 2024)
We are delighted to present the inaugural issue of The Saraswati Review: Contemporary Journal of English Language and Literature. This first edition brings together a rich array of critical perspectives, exploring themes such as identity, culture, trauma, and narrative innovation. We hope this issue sparks conversation and opens doors to further exploration in literary studies. This journal is born out of a shared passion for literature and critical inquiry. With this inaugural edition, we embark on a journey of exploration, dialogue, and discovery in the vast and ever-evolving field of English studies. We hope this issue inspires thoughts, generates curiosity, and invites fresh perspectives. It is our pleasure to share these works, and we look forward to growing alongside our readers and contributors. Thank you for being a part of our beginning. We look forward to many more volumes ahead. Thank You The Editorial Board